2015
DOI: 10.1039/c5cp02972d
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Fe3O4–Co3O4and Fe3O4–Mn3O4spinel solid solutions at the bulk and nanoscale

Abstract: High temperature oxide melt solution calorimetry has been performed to investigate the enthalpies of mixing (ΔmixH) of bulk and nanophase (1 -x)Fe3O4-xM3O4 (M = Co, Mn) spinel solid solutions. The entropies of mixing (ΔmixS) were calculated from the configurational entropies based on cation distributions, and the Gibbs free energies of mixing (ΔmixG) were obtained. The ΔmixH and ΔmixG for the (1 -x)Fe3O4-xCo3O4 system are negative over the complete solid solution range, for both macroscopic and nanoparticulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Fe 2+/3+ has a similar ionic radius as Mn 2+/3+ and can therefore easily occupy these free sites in the hausmannite type crystal structure, and the structure stays stable until 30% (atomic percent) of Fe. With higher Fe content, the tetragonal hausmannite becomes structurally unstable and transforms into a cubic spineltype crystal structure [43]. In the present study, small amounts of Fe are likely present in Mn 3 O 4 .…”
Section: Crmnfeconimentioning
confidence: 53%
“…Fe 2+/3+ has a similar ionic radius as Mn 2+/3+ and can therefore easily occupy these free sites in the hausmannite type crystal structure, and the structure stays stable until 30% (atomic percent) of Fe. With higher Fe content, the tetragonal hausmannite becomes structurally unstable and transforms into a cubic spineltype crystal structure [43]. In the present study, small amounts of Fe are likely present in Mn 3 O 4 .…”
Section: Crmnfeconimentioning
confidence: 53%
“…The drop solution enthalpies were measured in a custom‐made isoperibol Tian‐Calvet twin microcalorimeter described previously . Pellets of approximately 5 mg were loosely pressed, weighed on a microbalance, and dropped from room temperature into molten 3Na 2 O·4MoO 3 solvent at 702°C.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Miyahara attributed this anomalous behavior as arising from two opposing effects, namely a distortion with c / a >1 caused by the Mn 3+ ions at octahedral sites compensated by an opposing distortion with c/a <1 due to Cu 2+ ions at the tetrahedral sites . Investigations on Cu x Mn 3− x O 4 spinels revealed that Cu 2+ has a lower octahedral site preference than Mn 3+ and thus manganese has a greater tendency to occupy octahedral sites . Spinel ferrites, Cu x Fe 3− x O 4 , normally have a cubic structure, however it has been suggested that copper ferrite can exist in tetragonal form when annealed below 950°C .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the cation distribution in spinels is explained by the cation site preference. Based on literature data 31 , the Mn 3+ cations strongly prefer the octahedral sites, whereas Mn 2+ et Ga 3+ are randomly distributed over both tetrahedral and octahedral sites. The cation distribution in that case is given by (Mn 2+ 1…”
Section: 1structural Propertiesmentioning
confidence: 94%